Trigeminal Nerve Deficit in Large and Compressive Acoustic Neuromas and Its Correlation with MRI Findings. (1st August 2014) - Karkas, Alexandre; Lamblin, Eléa; Meyer, Mikael; Gay, Emmanuel; Ternier, Jessica; Schmerber, Sébastien
Abstract : Objectives: Evaluate the prevalence of preoperative trigeminal nerve deficit in large/compressive acoustic neuromas and try to find a correlation between pre/postoperative magnetic resonance imaging (MRI) findings and pre/postoperative trigeminal nerve deficit. Study Design: Case series with chart review. Setting: University medical center. Subjects and Methods: Retrospective study (1994‐2009) including patients with stage 4 or 5 acoustic neuromas (Zini‐Magnan classification). All patients underwent surgical resection. Pre‐ and postoperative trigeminal symptoms were sought. Imaging criteria were sought on pre‐ and 3‐month postoperative MRI scans. Pearson χ 2 statistical test was used. Results: Fifty‐three patients (27 females, mean 51 years) were operated on. Preoperatively, 3 patients (5.7%) had trigeminal neuralgia, 1 (1.9%) trigeminal anesthesia, and 28 (52.8%) trigeminal hypoesthesia. Sixteen patients (30.2%) had no corneal reflex (ophthalmic branch); keratitis occurred in 1 patient (1.9%). Postoperatively, 2 patients (3.8%) had trigeminal neuralgia, 1 (1.9%) trigeminal anesthesia, and 24 (45.3%) trigeminal hypoesthesia. Twenty‐six patients (49%) had no corneal reflex; keratitis occurred in 11 patients (20.7%). Preoperative trigeminal hypoesthesia was statistically correlated with impaction of the tumor on cerebellar peduncles on preoperative MRI. Postoperative trigeminal hypoesthesia was statistically correlated with nonvisibility of the trigeminal nerve on postoperative MRI. Conclusion: In large/compressive acoustic neuromas, trigeminal nerve deficit has to be sought to avoid corneal complications in particular. Trigeminal hypoesthesia occurs preoperatively in about half of the cases. It remains relatively stable after tumor removal, but there appears to be an increased rate of absent corneal reflex and keratitis postoperatively. We were able to correlate pre/postoperative trigeminal hypoesthesia with pre/postoperative MRI findings.